Synthesis and characterization of magnetic alginate microcapsules for lead adsorption - Ani Idris, author; Nur Suriani Mohd. Ismail, 1984-, author; Nursia Hassan, 1983-, author; Effaliza Misran, 1984-, author; Nanotech Malaysia Conference (2009 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL